2014
DOI: 10.1080/01919512.2014.956861
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot-Scale Application of Ozone to Bleach Raw Cotton Fabric Using Various Additives

Abstract: The influence of various additives on the efficiency of optimized ozone bleaching process at pilot scale has been discussed in this study. The results reveal that the best whiteness (63.79) and strength of bleached fabric is achieved with the addition of surfactant (2 g/L) at an ozone dose of 50 g/h, pH 5, and ozone treatment time of 45 min at room temperature. The dyeing quality of ozone-bleached and hydrogen peroxide-bleached fabric samples is almost identical. The analysis of variance of the experimental da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
0
12
0
3
Order By: Relevance
“…Ozone is a highly oxidative agent with an oxidation potential of 2.07 V. Several ozone applications were reported for textile finishing, such as clearing of disperse-dyed polyester [7][8][9][10][11], treatment of polylactic acid [12], soybean [13], rabbit [14], and wool [15] fibres, and bleaching of cotton [16][17][18][19][20]. Ozone is a highly oxidative agent with an oxidation potential of 2.07 V. Several ozone applications were reported for textile finishing, such as clearing of disperse-dyed polyester [7][8][9][10][11], treatment of polylactic acid [12], soybean [13], rabbit [14], and wool [15] fibres, and bleaching of cotton [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Ozone is a highly oxidative agent with an oxidation potential of 2.07 V. Several ozone applications were reported for textile finishing, such as clearing of disperse-dyed polyester [7][8][9][10][11], treatment of polylactic acid [12], soybean [13], rabbit [14], and wool [15] fibres, and bleaching of cotton [16][17][18][19][20]. Ozone is a highly oxidative agent with an oxidation potential of 2.07 V. Several ozone applications were reported for textile finishing, such as clearing of disperse-dyed polyester [7][8][9][10][11], treatment of polylactic acid [12], soybean [13], rabbit [14], and wool [15] fibres, and bleaching of cotton [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Na literatura foi estudada a eficácia do processo de ozônio com a adição de tensoativo em várias concentrações e foi constatado que a dosagem de 2 g/l de tensoativo apresentou o maior grau de branco e uma hidrofilidade de 10 segundos. Seus resultados mostraram que uma dosagem maior de 2 g/l de tensoativos diminui o grau de branco [27]. Portanto a adição do tensoativo na formulação de pré-alvejamento com ozônio facilita o contato do gás ozônio com os microporos do tecido através da diminuição da tensão superficial das fibras e aumenta a hidrofilidade, proporcionando um tingimento uniforme aos tecidos.…”
Section: Discussionunclassified
“…Na literatura foi mostrado que as notas de solidez a fricção dos tecidos de algodão tratados com ozônio também apresentaram valores similares às amostras tratadas pelo processo convencional [27]. O que leva a conclusão que o ozônio utilizado para pré-alvejar tecidos não interfere nos resultados de solidez dos tingimentos, o que, do ponto de vista da qualidade do produto ao uso, é muito importante.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Based upon the data published previously [23], NP treatments are shown to exhibit 'no effect' when the measured viability is greater than 50%, a 'moderate effect' when the viability ranges between 50 and 25%, and a 'strong effect' when viability below 25% is observed. Based upon the said standards, it was visually observed that the particles were non-cytotoxic even at 70μg/ml concentration, under dark conditions.…”
Section: Discussionmentioning
confidence: 99%